Case report: Subacute combined degeneration of the spinal cord due to nitrous oxide abuse - Wu, Huijuan; Huang, Huiqing; Xu, Liaoyang; Ji, Niu; Zhou, Xinyu; Xie, Kang (Frontiers in Neurology, 2023)
Background: Nitrous oxide (N2O) is an increasingly popular recreational drug. N2O irreversibly disturbs the metabolism of vitamin B12, resulting in a functional deficiency. Vitamin B12 is vital for myelin synthesis and its deficiency primarily produces neurological complications. Inhaling N2O is more common and neurological complications are more evident than before. Case presentation: We report a young man who developed progressive limb numbness and unsteady walking after N2O abuse. The dominant diagnosis was subacute combined degeneration of the spinal cord (SCD). The patient was admitted to the hospital and given adenosylcobalamin treatment, but his symptoms progressed significantly from before and he developed acute cognitive impairment. After methylprednisolone combined with vitamin B12 treatment, symptoms significantly improved. Conclusion: Clinicians need to understand the presentation and treatment of SCD caused by N2O abuse. When symptoms progress despite conventional vitamin B12 therapy, the combination of methylprednisolone and vitamin B12 may be considered.